KENDALI LQR DISKRIT UNTUK SISTEM TRANSMISI DATA DENGAN SUMBER JARINGAN TUNGGAL - Munawarroh, Dita Anies; ., Sutrisno (MATEMATIKA, 2014)
In this research discussed about control of data transmission systems with a single network source. Linier quadratic regulator (LQR) control with discrete time is used to control the systems. The linier quadratic regulator (LQR) control is optimal control with quadratic objective function and has linear constrains. The control has aim to optimizing the acceptance rate of data transmission. The data transmission systems have a single network source, can receive 100 % the entering data, although have time delay.